KAJIAN POLA SIRKULASI UNTUK SEKTOR INFORMAL DI RUANG TERBUKA PUBLIK KORIDOR YOS SUDARSO KOTA PALANGKARAYA - Noor Hamidah (Diponegoro University, 2012)
This street Yos Sudarso is an important part of Palangka Raya urban growth history (Cilik Riwut, 1971). This research objective is to find of method for design of circulation pattern and architecture landscape for informal sector in along for Yos Sudarso Street. The output is this research will be able to approve how is important of public open space, ecology and infrastructure. This research method will use literature review, field observation, interview and quesioner. This research had been done in last year with focus in function of public open space. The stage of this research consist of: 1) preparation; 2)literature review; 3) analysis; 4) concept of public open space, concept of circulation pattern and concept of sector informal in public open space. This research will give information of physic consist of: (a) Design of circulation pattern in public open space; (b) design of parking area and pedestrian; (c) design building of informal sector (d) design ofstreet furniture in public open space. Non-physic will give information consist of: (a) social aspect; (b) economy aspect dan (c) ecology aspect.